Investigating the sustainability of medicinal plants and the loss of traditional knowledge in a rural community in Namaqualand - Goldberg, Karen (Department of Biological Sciences, 2017)
Up until the early 1990s conservation practices in South Africa were culturally biased, focusing largely on the value systems of the affluent. However, with the release in 1997 of the White Paper on the Conservation and Sustainable Use of South Africa's Biological diversity, the role that biological resources play in providing for the needs of all South Africans, is now emphasized. According to this policy, human needs must be considered if conservation is to be successfully implemented. Using this document as the framework for this study I chose to investigate various aspects of medicinal plant use in a rural community in Paulshoek, Namaqualand. The main aims were as follows: to evaluate the local knowledge regarding medicinal plants; to document the plants used and collected in Paulshoek; and to determine potential threats to the biological resource. This was achieved by employing a variety of social and ecological methods. It became apparent from the interactions and interviews with the residents that medicinal plants are an important resource to the Paulshoek community since more than 70% of the population regularly use herbal remedies. While there is some evidence to suggest that the local knowledge of medicinal plants is dying out, I would speculate that most of the knowledge has already been lost. Of the 15 plants used and collected in Paulshoek, most appear to be highly sustainable in the landscape. This conclusion was based on people's perceptions regarding the change in abundance of each of these species over time and by further comparing plant size between Paulshoek and adjacent commercial farms. As most medicinal species seem unaffected by either: harvesting or land use practices this indicates that it is possible to achieve a sustainable harvest. Certain species do, however, show evidence of decline. Fuelwood harvesting most probably accounts for the change in abundance of Rhus burchelli over time, while Mentha longifolia may be facing some reduction in plant fitness due to harvesting for medicinal purposes. Sceletium emarcidum is on the verge of local extinction due to a combination of intensive harvesting and high grazing pressures. In contrast, high stocking densities appear to account for the increased abundance in both Galenia africana and Ballota africana. These findings clearly show that while the resource as a whole may be fairly resilient to harvesting and land use practices, certain species are in need of urgent conservation. This study further highlights the need to look beyond the direct impacts of harvesting and consider all possible threats, if the resource is to be sustainably managed. While this case study is atypical of the state of the medicinal plant resource in most of South Africa, this survey serves as a novel protocol for evaluating the sustainability of any resource which is regularly utilized.